Overcoming threats to the economic security of Ukraine in the process of creating conditions for the preservation and development of labor potential on the basis of resilience - Novikova, O.; Ostafiichuk, Yа.; Azmuk, N.; Pankova, O.; Kasperovych, O. (Економічний вісник Донбасу, 2025)
The article reveals the conceptual foundations of labor resource security, its essence, role, and significance within the structure of Ukraine’s economic security under conditions of protracted war and post-war reconstruction. The study substantiates the need and importance of ensuring the resilience of labor resource security for the effective functioning, recovery, and development of the national economy. Particular attention is paid to the problem of an acute labor shortage caused by human losses and migration processes resulting from the war. The necessity of a deep and comprehensive integration of labor resource security into the system of economic security components of the state – namely, its macroeconomic, financial, scientific and technological, production, social, demographic, and regional subsystems – is justified. Strategic areas for overcoming threats in the labor sphere based on the principles of resilience are proposed. The authors recommend that labor resource security should be integrated into the framework of fundamental policy documents, including the Strategy of Economic Security of Ukraine until 2030 and the Action Plan for the Implementation of the National Resilience System. У статті розкрито концептуальні основи безпеки трудових ресурсів, її сутність, роль та значення в структурі економічної безпеки України в умовах тривалої війни та повоєнної відбудови. У дослідженні обґрунтовано необхідність та важливість забезпечення стійкості безпеки трудових ресурсів для ефективного функціонування, відновлення та розвитку національної економіки. Особлива увага приділяється проблемі гострого дефіциту робочої сили, спричиненого людськими втратами та міграційними процесами, що виникли внаслідок війни. Обґрунтовано необхідність глибокої та всебічної інтеграції безпеки трудових ресурсів у систему складових економічної безпеки держави, а саме: її макроекономічну, фінансову, науково-технологічну, виробничу, соціальну, демографічну та регіональну підсистеми. Запропоновано стратегічні напрямки подолання загроз у сфері праці на основі принципів стійкості. Автори рекомендують інтегрувати безпеку трудових ресурсів у рамки основоположних програмних документів, зокрема Стратегії економічної безпеки України до 2030 року та Плану дій щодо впровадження Національної системи стійкості.